Pengaruh Pemberian Umpan dan Daun Salam (Syzygium polyanthum) terhadap Perilaku Kecoa Amerika (Periplaneta americana) - Dwi, Yohanna Aresta; Ramli, Murni (Universitas Sebelas Maret, 2022)
This study aims to determine the behavior caused by the American cockroach (Periplaneta americana) due to bait and bay leaf (Syzygium polyanthum). The research method used is a quantitative (experimental) method using a completely randomized design (CRD) consisting of 3 treatments with 3 times variations. The results showed the behavior of cockroaches that approached the bait and bay leaf. In the first treatment (P1) as a control in the form of 5 grams of bait showed clear results that the behavior of the cockroach approached the bait. In the second treatment (P2) in the form of 5 grams of bait and 3 grams of bay leaves showed a repellent power of 20%. While in the three treatments (P3) in the form of 5 grams of bait and 10 grams of bay leaves, the repellant power was 26.67%. Based on this, the bay leaf is still less effective to be used as a natural cockroach repellent or repellent. So it can be said that the provision of bait and bay leaf (Syzygium polyanthum) to the American cockroach (Periplaneta americana) resulted in similar behavior.